Methodological Support Using Innovative Teaching for The Development of Natural and Scientific Outlook of Students methodological Support Using Innovative Teaching for The Development Of Natural And Scientific Outlook Of Students - Rakhimov, A. K.; Jononova, R. N.; Egamberdieva, L. N. (International Journal of Psychosocial Rehabilitation, 2020)
This article has been written in order to report on the findings of a research carried out to develop and implement methodological support of the “Evolutionary Teaching” course in accordance with the requirements of the didactic fundamentals of innovative learning environments; use innovation and information technology effectively in the teaching process, organize independent study of students gradually and effectively, provide prevalence of and establish dynamics of development of natural and scientific outlook, and increase the efficiency of these all.